The Chelsea girls : a novel - Davis, Fiona, 1966- (Dutton, 2019)
"From the dramatic redbrick facade to the sweeping staircase dripping with art, the Chelsea Hotel has long been New York City's creative oasis for the many artists, writers, musicians, actors, filmmakers, and poets who have called it home--a scene playwright Hazel Riley and actress Maxine Mead are determined to use to their advantage. Yet they soon discover that the greatest obstacle to putting up a show on Broadway has nothing to do with their art, and everything to do with politics. A Red scare is sweeping across America, and Senator Joseph McCarthy has started a witch hunt for Communists, with those in the entertainment industry in the crosshairs. As the pressure builds to name names, it is more than Hazel and Maxine's Broadway dreams that may suffer as they grapple with the terrible consequences, but also their livelihood, their friendship, and even their freedom. Spanning from the 1940s to the 1960s, The Chelsea Girls deftly pulls back the curtain on the desperate political pressures of McCarthyism, the complicated bonds of female friendship, and the siren call of the uninhibited Chelsea Hotel"--